2009
DOI: 10.1007/s00572-009-0280-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of culture conditions of Arnica montana L.: effects of mycorrhizal fungi and competing plants

Abstract: Arnica montana is a rare plant that needs special protection because of its intensive harvesting for medicinal purposes. The present work was aimed at finding optimal culture conditions for Arnica plants in order to enable their successful reintroduction into their natural stands. Plants were cultivated under controlled greenhouse conditions on substrata with different nitrogen (N) concentration. As Arnica is always colonized by arbuscular mycorrhizal fungi (AMF) in nature, a fact that has been overlooked in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Contents of these unique ingredients can be used as standards for the quality of medicinal plants, such as levels of limonene and carvone in dill (Kapoor et al 2002a), thymol in carum (Kapoor et al 2002a), geraniol and linalool in coriander (Kapoor et al 2002b), anethol in fennel (Kapoor et al 2004), sesquiterpene lactones in Arnica (Jurkiewicz et al 2010), and artemisinin in A. annua (Kapoor et al 2007;Chaudhary et al 2008;Huang et al 2011). Previous research has shown that the AM symbiosis can promote the production of specific secondary metabolites in specific medicinal plants.…”
Section: Terpenesmentioning
confidence: 99%
See 3 more Smart Citations
“…Contents of these unique ingredients can be used as standards for the quality of medicinal plants, such as levels of limonene and carvone in dill (Kapoor et al 2002a), thymol in carum (Kapoor et al 2002a), geraniol and linalool in coriander (Kapoor et al 2002b), anethol in fennel (Kapoor et al 2004), sesquiterpene lactones in Arnica (Jurkiewicz et al 2010), and artemisinin in A. annua (Kapoor et al 2007;Chaudhary et al 2008;Huang et al 2011). Previous research has shown that the AM symbiosis can promote the production of specific secondary metabolites in specific medicinal plants.…”
Section: Terpenesmentioning
confidence: 99%
“…Resisting malaria Kapoor et al 2007;Rapparini et al 2008;Chaudhary et al 2008;Awasthi et al 2011;Huang et al 2011 Echinacea purpurea Antibacterial and antiviral effects Araim et al 2009 Arnica montana Treating bruises, swellings and diseases of the mouth Jurkiewicz et al 2010 Inula ensifolia Diminishing inflammation and antiviral effect Zubek et al 2010 Artemisia umbelliformis Antibacterial and antiviral effects Binet et al 2011 Tagetes erecta Diminishing inflammation, treating cold and cough…”
Section: Camptotheca Acuminatamentioning
confidence: 99%
See 2 more Smart Citations
“…The polyacetylenic molecules additionally provide an antifungal effect. Phenolic acids add an antioxidative facet (Rossetti et al 1984;Teuscher et al 2009;Jurkiewicz et al 2010;Pljevljakušić et al 2012). …”
Section: Discussionmentioning
confidence: 99%